Early mobilization in the intensive care unit: Systematic Review (Research, Society and Development, 2022)
The present study is a systematic review whose purpose was to analyze the studies on the use of Early Mobilization (PM) intervention in intensive care bed patients, identify its benefits and recognize the main protocols currently used for patient recovery. A systematic qualitative observational and cross-sectional analysis of studies addressing early mobilization in ICU beds was performed. The results of the study showed that Early Mobilization is an effective treatment regarding the first care of the physiotherapist for the patient in the ICU. Studies such as that of Zhu et al. (2018) are of relevant importance for the area of physiotherapy, where the intervention of MP in patients in the ICU can be effective and reduce their length of stay in bed.